Do the Global Oil Price Shocks Affect Somalia's Unregulated Exchange Rate Volatility? - Nor, Mohamed Ibrahim; Masron, Tajul Ariffin (International Journal of Energy Economics and Policy, 2018)
The aim of this study to investigate the impact of global oil price shocks on Somalia's unregulated exchange rate volatility. While employing an EGARCH model, the study found that global oil price shocks have significant effect on Somalia's unregulated exchange rate volatility. This suggests that the effect of energy shocks is global phenomenon beyond the control of any regulatory authority and/or trade treats. The results of this paper provide a notable contribution to the literature of energy economics as well as monetary economics. The research also calls for the need of reforming and re-building Somalia's foreign exchange system to withstand the unpredictable shocks of the global oil markets. Furthermore, this study implies that even in times of war and lawlessness, we cannot escape the effect of global energy price shocks. This is an interesting noble contribution that would be worth considering in the energy and economic literature. Keywords: Exchange Rate Volatility; global oil price; unregulated exchange rate JEL Classifications: E00; F31; Q43; G15; O13; P18